Knowledge, attitude, and practice on paederus dermatitis among students in UiTM Puncak Alam, Selangor / Nur Syakira Shaharuddin and Azwandi Ahmad - Shaharuddin, Nur Syakira; Ahmad, Azwandi (Faculty of Pharmacy, 2021)
Paederus dermatitis is a skin disease caused by staphylinids beetle (Coleoptera: Staphylinidae) from the genus Paederus. Paederus dermatitis cases have been reported in Malaysia, especially among university students including Universiti Teknologi MARA (UiTM). Therefore, this study was carried out to access the current level of knowledge, attitude, and practice (KAP) on paederus dermatitis among UiTM Puncak Alam students. Besides, we also compared the level of knowledge, attitude, and practice on paederus dermatitis among students from different faculties and residential colleges s in UiTM Puncak Alam. A cross-sectional survey was conducted on 388 undergraduate students from September 2019 until July 2020. The majority of the students have an adequate level of knowledge and practice while a moderate level of attitude towards paederus dermatitis. There was a significant positive correlation between knowledge and attitude on paederus dermatitis (p<0.05). Data showed that knowledge and attitude regarding paederus dermatitis were significantly different between faculties (p<0.05). Students from the Faculty of Pharmacy have better knowledge and attitude score compared to the accountancy students. There was a significant influence of residence college on practice towards paederus dermatitis (p<0.05). Students staying at Dahlia college have the best practice followed by Casuarina, Angsana, and Rafflesia. In conclusion, awareness and educational programs regarding paederus dermatitis should be done by targeting students from different faculties and hostels. The effort also must be put to translate the components of good knowledge into a good attitude and practice of paederus dermatitis.